Land Acquisition Policy for Public Interest from a Human Rights Perspective - Rafiqi Rafiqi; Windy Sri Wahyuni (JURNAL AKTA, 2026)
This article examines land acquisition policies for public interest from a human rights perspective. Although land acquisition is essential for national development, its implementation often generates agrarian conflicts and potential violations of land rights. This situation reflects the tension between development objectives and the obligation to protect the rights of affected communities. This study aims to analyze the conformity of land acquisition policies for public interest with human rights principles and to assess legal protection for affected communities. It also seeks to formulate recommendations for land acquisition policies that promote justice and ensure the respect and protection of human rights. This research adopts a normative legal method using statutory, conceptual, and human rights approaches. The study is based on a literature review of laws and regulations, legal doctrines, court decisions, and national and international human rights instruments related to land acquisition. What The main findings of this study indicate that land acquisition policies for public interest in Indonesia tend to emphasize procedural legality rather than substantive justice, particularly in protecting the rights of affected communities. The research reveals that limitations in meaningful participation and fair compensation weaken human rights protection. The novelty of this study lies in positioning human rights principles as substantive evaluative benchmarks for land acquisition policies, offering an original contribution to strengthening agrarian justice within the existing legal framework.